IRIS MURDOCK "CALL": ARTISTIC ANALYSIS OF THE IMAGE OF DORA - RASULOVA GULBAHOR KERIMBAEVNA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyzes the dynamics of the image of Dora, one of the protagonists of Iris Murdock’s novel The Bell, growing and changing in different situations and events. At the beginning of the novel, the author informs the reader about Dora’s subjective image by giving her a subjective image, and then with the help of an external image she is able to behave in several situations. Also, some features of this image, the role of space, place and other images in their opening, as well as the artistic and aesthetic function are revealed.